The emerging role of hypoxia-inducible factor-2 involved in chemo/radioresistance in solid tumors. Issue 7 (July 2015) - Zhao, Jiuda; Du, Feng; Luo, Yang; Shen, Guoshuang; Zheng, Fangchao; Xu, Binghe
Highlights We first summarize the contribution of HIF-2α in chemo/radioresistance in solid tumors. Studies assessing the roles of HIF-2α on drug resistance are scarce compared to those on HIF-1 in solid tumors. Some new mechanisms contribute to HIF-2 resistance to chemo/radioresistance. We further discuss HIF-2 inhibitors and the different mechanisms of HIF-2- and HIF-1-mediated chemo/radioresistance.